High-precision trajectory tracking design and simulation for six degree of freedom robot based on improved active disturbance rejection control. (May 2019) - Chen, Fengjun; Liao, Jinqi; Xiong, Jun; Yin, Shaohui; Huang, Shuai; Tang, Qingchun
High-precision trajectory tracking control is an important factor in the performance of industrial robots. In this study, a high-precision trajectory tracking strategy was proposed for controlling a degree of freedom serial robot on the basis of improved active disturbance rejection control. An independent control strategy of a single joint was adopted, and the corresponding decoupling control law was designed. An attitude trajectory-planning algorithm based on the circular-blending quaternion curve was improved. The position and attitude trajectories were transformed into the joint trajectory by using a kinematics equation and inverse velocity Jacobian matrix. The above-mentioned transformation link was used as a preprocessing link of the active disturbance rejection control, which is used for replacing the tracking differentiator of a typical active disturbance rejection control to eliminate the effect of the tracking delay. An experimental simulation was conducted by combining MATLAB and ADAMS. Simulation results show that the proposed control strategy can perform the tracking control of a task-space trajectory. The tracking precision of position and attitude trajectories were 0.01 mm and 0.01 s, respectively.